Vascular tone auto-regulation in young men with arterial hypertension: antihypertensive therapy effects - I. M. Davidovich; O. V. Afonaskov; E. V. Porotikova (Кардиоваскулярная терапия и профилактика, 2011)
Aim. To assess vaso-regulating endothelial function and vascular tone auto-regulation status, in regard to arterial hypertension (AH) duration and stage, as well as to investigate the respective effects of antihypertensive therapy (AHT), in young men with AH. Material and methods. The study included 49 men with Stage I-II AH (mean age 39,3±0,8 years), not treated before or treated irregularly. The controls were 22 men with normal blood pressure (BP) levels (mean age 37,5±1,7 years). The examination included 24-hour BP monitoring (BPM) and assessment of endothelium-dependent vasodilatation (EDVD) and time-adjusted mean arterial velocity (TAMX) in functional tests. Results. In young men with Stage I-II AH, in contrast to normotensive men, EDVD and reactivity indices (RIs) were decreased in functional TAMX assessment tests. These changes in EDVD and RIs were observed even in patients with relatively short AH duration or Stage I AH. Effective AHT resulted not only in target BP level achievement, but also in normalisation of EDVD and vascular tone auto-regulation. Conclusion. ACE inhibitors (lisinopril and enalapril) normalised EDVD and vascular tone auto-regulation parameters in young men with AH.